The Effects of Using Thyme on Iron Status in the Elite Sportsmen - Hazar, Serkan; Alpay, C. Berkan (Pakistan Journal of Nutrition, 2011)
This study aims to investigate the effects of using thyme on iron and iron related hematological parameters elite athletes. The subject group of the research was composed of 12 male wrestlers who have competed in various age categories of Turkish National Team and who were still competent for the medal in Turkey Championships. The subjects, all of whom have been carrying out actively, for at least 2 months, their applicable exercises were subjected to the thyme loading session without any interference in their training sessions. Each person was offered after meals, three times a day for duration of 35 days total, thyme tea which had been brewed 1 gram dried thyme in boiled water of 150 cm3 for ten minutes. Before and after the thyme loading period, blood samples were collected and analyzed the levels of Hemoglobin (HGB), Erythrocyte (RBC), Ferritin (F), Transferrin (T) Serum Iron (SI) and Iron Binding Capacity (IBC) was accomplished by means of the brand OLYPUS AU640 hemacytometer. The amount of Transferrin Saturation (TS) was calculated using the formula, “SI X 100/IBC”. In this study it was observed that the applicable levels were within, before and after thyme loading, the normal clinical values. However, a significant decrease, after 4-week thyme loading, for the concentration levels of HGB, RBC and SI (p<0.05) and a significant increase for the level of IBC (p<0.01) were identified. As a result, it was observed that the thyme which has been known for its numerous benefits has, besides its positive effects, some adverse effects on the iron status in the sportsmen. Therefore, supplemental iron loading, coupled with giving beverages such as tea, green tea, thyme, etc. all containing catechin as active substance might be required for the performance sportsmen.